Survival and growth of the sea cucumber holothuria scabra (Jaeger) juveniles reared at different diets - Baylon, Basil (2009.)
In this study, the effects of five diets on growth and survival of sea cucumber Holothuria scabra juveniles were compared. The five treatments used were benthic diatoms (Navicula sp.) alone, combination of benthic diatoms and seaweed (Sargassum sp.) extract alone, combination of benthic diatoms and seagrass Thalassia sp.) extract, and commercial shrimp feed.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Sea cucumber (Holothuria scabra)